Antibiotic resistance and pathogenic bacterial profiles in drinking and surface water in Baghdad, Iraq. - Wael Obaid; Anmar Khalaf; Jilan Shakur (Microbes and Infectious Diseases)
Background: Aquatic environments serve as hotspots for the dissemination of genes and micro-organisms that are resistant to antibiotics. The research sought to assess the microbiological quality of various water sources. Methods: The samples were analyzed for their physicochemical parameters. Standard procedures were used to enumerate and characterize pathogenic bacteria, nonfermentors, and fecal coliforms. The susceptibility of isolated bacteria to thirteen antibiotics was tested using disk diffusion techniques. Results: The results showed that water's pH values ranged between 6.4 and 8, while turbidity values varied from 0.88 to 9.21 NTU. The recorded electrical conductivity ranged from 52.5 to 602.4 S/cm, while the total suspended solids (TSS) values varied from 240 to 900 mg/l. Furthermore, the present findings show that chloride concentrations ranged between 188.565 and 474.866 mg/l, and dissolved oxygen levels ranged from 3.66 to 8.56 mg/l. These findings comply with the permissible limits set by WHO and Iraqi guidelines. The results were alarming for drinking water supply, surface water, residential well water, and household borehole water, with 100%, 70%, 40%, and 20% positive results, respectively. However, we detected 180 bacterial strains (20%) Klebsiella. pneumoniae, (16%) Pseudomonas aeruginosa, (16%) Escherichia coli, (6%) Legionella pneumophila, (5.6%) Citrobacter spp., (5.2%) Vibrio cholera, and (4%) Aeromonas spp.  In addition, among 80 coliform, 56.25% were fecal coliforms, while 81.25% were total coliforms. The highest percentage of resistance was observed against ceftriaxone, ciprofloxacin, and imipenem/cilastatin (100%), cefoperazone/sulbactam comes in second at 95%, cefepime/tazobactam 92%, norfloxacin 90% and ofloxacin 90%. the lowest degree of resistance against piperacillin/tazobactam, colistin, cefotaxime, and gentamicin (47%), representing 40%, 42%, 45%, and 47%, respectively. Nonfermenting bacteria demonstrated that the strains were 100% resistant to Trimethoprim Sulfamethoxazole, cefoperazone/sulbactam, ciprofloxacin, and cefepime/tazobactam. The coliforms isolates were 100% resistant to ampicillin, cefoperazone/sulbactam, and norfloxacin. Conclusions: The health of community members who depend on these initiatives for their drinking water may be threatened by an abundance of antibiotic-resistant bacteria and pathogenic microbes. Our findings underscore the pressing necessity for enhanced water purification, more stringent limits on antibiotic usage, and improved surveillance to curtail the proliferation of resistance. The research underscores the significance of cohesive public health strategies and the creation of efficient monitoring and diagnostic instruments to tackle the escalating issue of aquatic antibiotic resistance.